2011
DOI: 10.1016/j.biomaterials.2011.07.049
|View full text |Cite
|
Sign up to set email alerts
|

Effects of hypoxias and scaffold architecture on rabbit mesenchymal stem cell differentiation towards a nucleus pulposus-like phenotype

Abstract: Nucleus pulposus grafts are needed for patients requiring replacement of their degenerated intervertebral discs. Bone marrow-derived mesenchymal stem cells (MSCs) are potential autologous stem cell source for the nucleus pulposus regeneration. One of the key issues of constructing functional nucleus pulposus using MSCs, however, is to differentiate MSCs into nucleus pulposus phenotype in vitro and to maintain their phenotypic stability in vivo. In this study, three-dimensional (3D) nanofibrous poly(L-lactide) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
66
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 64 publications
(67 citation statements)
references
References 32 publications
1
66
0
Order By: Relevance
“…However, the same organization also indicates that the term MSCs may be used. To promote differentiation of animal or human MSCs, several methods were developed which involved growth factors from the transforming growth factor family (15)(16)(17)(18). An alternative approach is the co-culture of IVD cells with MSCs in the 'one-surface system' (also known as direct co-culture or contact system), three-dimensional systems (alginate beads) and culture of two cell lines separated by a porous membrane (also termed insert system, indirect co-culture or non-contact system) (19).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, the same organization also indicates that the term MSCs may be used. To promote differentiation of animal or human MSCs, several methods were developed which involved growth factors from the transforming growth factor family (15)(16)(17)(18). An alternative approach is the co-culture of IVD cells with MSCs in the 'one-surface system' (also known as direct co-culture or contact system), three-dimensional systems (alginate beads) and culture of two cell lines separated by a porous membrane (also termed insert system, indirect co-culture or non-contact system) (19).…”
Section: Discussionmentioning
confidence: 99%
“…An alternative approach is the co-culture of IVD cells with MSCs in the 'one-surface system' (also known as direct co-culture or contact system), three-dimensional systems (alginate beads) and culture of two cell lines separated by a porous membrane (also termed insert system, indirect co-culture or non-contact system) (19). Injection of MSCs into the disc space was also assayed (16,20).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In our previous studies, the nanofibrous architecture was shown to provide physical cues to enhance mesenchymal stem cell differentiation into a nucleus pulposus phenotype. 3 The current study proved that the low oxygen tension and the 3D nanofibrous scaffolds could mimic the physiological environment existing in the intervertebral disc to synergistically regenerate nucleus pulposus tissue. Fig.…”
Section: Discussionmentioning
confidence: 55%
“…Badylak et al, 1995;Dejardin et al, 2001;Jonsson et al, 2011;Kim et al, 2012;Kim et al, 2014b ; Ledet et al, 2009;Visage et al, 2006 Danhier et al, 2012;El-Amin et al, 2003;Endres et al, 2010;Feng et al, 2011;Kim et al, 2014a;Lai et al, 2014;Liang et al, 2013;Mizuno et al, 2004;Ruan et al, 2010 Poly-ε- Sinha et al, 2004;Silva et al, 2007;Li et al, 2005a;Lopez et al, 2010;Koepsell et al, 2011a ;Koepsell et al, 2011b;Martin et al, 2014 Martino et al, 2005). However, chitosan gels tend to be much softer and...…”
Section: Natural Solid Biomaterialsmentioning
confidence: 99%